2011
DOI: 10.1089/cyber.2009.0382
|View full text |Cite
|
Sign up to set email alerts
|

Use of Social-Networking Sites and Subjective Well-Being: A Study in South Korea

Abstract: Social-networking sites (SNSs) provide users with a unique computer-mediated environment where individuals are able to disclose their thoughts, feelings, and experiences within their circle of personal ties. From a positive psychological perspective, this research investigated the use of SNSs and users' subjective well-being. The results show that although the time spent using a SNS is not related to well-being, the amount of self-disclosure on SNSs is positively related to subjective well-being. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
2
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(99 citation statements)
references
References 29 publications
6
83
2
8
Order By: Relevance
“…[32][33][34][35][36][37] As shown by the behavioral measures of this study, the social and psychological consequences of SNS use are contingent on the way in which people use these platforms. While mere consumption is associated with reduced closeness, active participation seems to increase the feeling of closeness and positive emotions.…”
Section: Discussionmentioning
confidence: 80%
“…[32][33][34][35][36][37] As shown by the behavioral measures of this study, the social and psychological consequences of SNS use are contingent on the way in which people use these platforms. While mere consumption is associated with reduced closeness, active participation seems to increase the feeling of closeness and positive emotions.…”
Section: Discussionmentioning
confidence: 80%
“…The primary motivation for using social Internet applications relates to the maintenance of established offline networks (Donath & boyd, 2004;Ellison, Steinfield, & Lampe, 2007). Previous research indicates that these motivations differ between age groups, with young adolescents expressing their identities by means of a selfdisplay of personal information and older adolescents expressing it through connections (Lee, Lee, & Kwon, 2010). However, unlike the hypothesised relationship, the use of social applications other than SNSs and Twitter did not contribute to predicting Internet addiction.…”
Section: Discussionmentioning
confidence: 84%
“…Also using a Dutch sample, Vergeer and Pelzer (2009) showed that online network capital had the effect of enhancing offline network capital, although there was no significant relationship between online network capital and loneliness. Time spent at CyWorld, a popular SNS in Korea, did not correlate with subjective well-being including negative affect, positive affect, or satisfaction with life (Lee, Lee, & Kwon, 2011), but there was a positive correlation between SNS network size and subjective well-being.…”
Section: Cultural Differences In Connection Demands and Impactsmentioning
confidence: 82%